Outcomes of a National Faculty Development Program in Teaching Skills: Prospective Follow-up of 110 Internal Medicine Faculty Development Teams - Houston, Thomas K (Blackwell Science Inc, 2004)
BACKGROUND: Awareness of the need for ambulatory care teaching skills training for clinician-educators is increasing. A recent Health Resources and Services Administration (HRSA)-funded national initiative trained 110 teams from U.S. teaching hospitals to implement local faculty development (FD) in teaching skills. OBJECTIVE: To assess the rate of successful implementation of local FD initiatives by these teams. METHODS: A prospective observational study followed the 110 teams for up to 24 months. Self-reported implementation, our outcome, was defined as the time from the training conference until the team reported that implementation of their FD project was completely accomplished. Factors associated with success were assessed using Kaplan-Meier analysis. RESULTS: The median follow-up was 18 months. Fifty-nine of the teams (54%) implemented their local FD project and subsequently trained over 1,400 faculty, of whom over 500 were community based. Teams that implemented their FD projects were more likely than those that did not to have the following attributes: met more frequently (P=.001), had less turnover (P=.01), had protected time (P=.01), rated their likelihood of success high (P=.03), had some project or institutional funding for FD (P=.03), and came from institutions with more than 75 department of medicine faculty (P=.03). The cost to the HRSA wwas $22,033 per successful team and $533 per faculty member trained. CONCLUSIONS: This national initiative was able to disseminate teaching skills training to large numbers of faculty at modest cost. Smaller teaching hospitals may have limited success without additional support or targeted funding.